TINDAK KEJAHATAN CYBERBULLYING MELALUI MEDIA ELEKTRONIK BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Arbainsyah Arbainsyah (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTCyberbullying crimes happens because the rise of the Internet users, especially social networking users (Facebook, Twitter, and other) without some basic knowledge of ethics in the use of Internet technology.The formulation of the problem are why cyberbullying is a crime and how to manage cyberbullying crimes on law number 11 of 2008 on Information and Electronic Transactions.The research found that cyberbullying has any impact that can not be underestimated, cyberbullying that happen continuously can lead to prolonged depression that would eventually lead to the victim wishes to undertake extreme measures, like to end their lives by suicide. Cyberbullying crimes in Indonesia has legal provisions and sanctions has been regulated in Law Number 11 of 2008 on Information and Electronic Transactions.Based on the matter is expected that Internet users especially social networking users can more prudence in using internet technology, so the crime of cyberbullying can be avoided. Key words: Cyberbullying , Cybercrime